Application of Criminal Sanctions Against Perpetrators of the Crime of Destruction (Vandalism) at the Long Port Loading and Unloading Workforce Cooperative Office (Decision Study Number: 1199/Pid.B/2021/PN.Tjk) - Evan Ruzyantara; Zulfi Diane Zaini; Intan Nurina Seftiniara (CV. Rayyan Dwi Bharata, 2023)
This type of crime of destruction or vandalism is one of the most common crimes in society, which occurs in almost every region in Indonesia. The problem in this research is how to apply criminal sanctions to the perpetrators of the crime of vandalism at the Cooperative Office for loading and unloading workers at the port of Panjang (Decision Study Number: 1199/Pid.B/2021/PN.Tjk), as well as the judge's considerations in passing a decision on the perpetrators of the crime of vandalism at the Cooperative Office for loading and unloading workers at the Long Port (Decision Study Number: 1199/Pid.B/2021/ PN.Tjk). This research includes qualitative research. Qualitative methods allow researchers to get to know people or individuals firsthand and watch them as they express opinions and draw conclusions. Application of criminal sanctions against perpetrators of criminal acts of destruction (vandalism) at the Long Port Loading and Unloading Workforce Cooperative Office, Defendant AN who is proven guilty where the Defendant has violated and fulfilled the elements in Article 406 paragraph (1) of the Criminal Code accompanied by good legal facts through the testimony of the Defendant, witnesses and evidence available at trial. The application of material criminal sanctions applied by judges based on the elements of Article 406 of the Criminal Code is appropriate and fulfilled. Thus, according to the author, the accused has received a deterrent effect and has not repeated his actions.